Laser weeding of common weed species - Andreasen, Christian; Vlassi, Eleni; Salehan, Najmeh (Frontiers in Plant Science, 2024)
The massive use of herbicides since the 1950s has resulted in increasing problems with herbicideresistant weeds and pollution of the environment, including food, feed, and water. These side effects have resulted in political pressures to reduce herbicide application. The European Commission aims to reduce the use and risk of chemicals and more hazardous pesticides in the EU. Therefore, new weed control methods are in demand. Laser weeding might be an alternative to replace or supplementbstitute herbicides and other weed control methods in an Integrated Weed Management (IPM) strategy. This work aimed to investigate how increasing laser energy affected common weeds when the apical meristem was exposed to irradiation at the early stages of development. A 50 W thulium-doped fibre laser with a diameter of 2 mm and a wavelength of 2 µm was used. The highest efficacybest effect of laser irradiation was achieved when the grass weed (Alopecurus myosuroides) had one leaf and the dicot species were at the cotyledon stage. There was a large difference between the species' susceptibility to irradiation probably caused by differences in morphology and growth habit. At the 4leaf stage, most of the species regrew after laser applicationirradiation. Laser weeding may be a solution to replace or supplementbstitute other weed control methods in some crops, but in general the weeds must be irradiated when they are at the cotyledon to 2 leaf stagesmall to avoid regrowth.